At-grade stabilization structure impact on surface water quality of an agricultural watershed. (15th April 2015) - Minks, Kyle R.; Ruark, Matthew D.; Lowery, Birl; Madison, Fred W.; Frame, Dennis; Stuntebeck, Todd D.; Komiskey, Matthew J.; Kraft, George J.
Abstract: Decades of farming and fertilization of farm land in the unglaciated/Driftless Area (DA) of southwestern Wisconsin have resulted in the build-up of P and to some extent, N, in soils. This build-up, combined with steep topography and upper and lower elevation farming (tiered farming), exacerbates problems associated with runoff and nutrient transport in these landscapes. Use of an at-grade stabilization structure (AGSS) as an additional conservation practice to contour strip cropping and no-tillage, proved to be successful in reducing organic and sediment bound N and P within an agricultural watershed located in the DA. The research site was designed as a paired watershed study, in which monitoring stations were installed on the perennial streams draining both control and treatment watersheds. Linear mixed effects statistics were used to determine significant changes in nutrient concentrations before and after installation of an AGSS. Results indicate a significant reduction in storm event total P (TP) concentrations ( P  = 0.01) within the agricultural watershed after installation of the AGSS, but not total dissolved P ( P  = 0.23). This indicates that the reduction in P concentration is that of the particulate form. Storm event organic N concentrations were also significantly reduced ( P  = 0.03) after the AGSS was installed. We conclude that AGSS was successful in reducing the organic and sediment bound N and P concentrations in runoff waters thus reducing their delivery to nearby surface waters. Highlights: At-grade stabilization structures reduced particulate P concentration in runoff. Storm event organic N concentrations were significantly reduced with AGSS. At-grade stabilization structures did not reduce inorganic N concentrations.